La alfabetización científica en los cursos de licenciatura en ciencias de las universidades federales del noreste de Brasil - Oliveira Nunes, Albino (2025)
This study analyzes the Pedagogical Course Projects (PPCs) of federal universities in northeastern Brazil in the fields of biological sciences, physics, and chemistry, seeking evidence of Scientific Literacy (SL) in graduate profiles and course objectives. The research employed the lexical analysis software IRaMuTeQ to conduct similarity analyses and Descending Hierarchical Classification (DHC). The findings indicate that, although SL is present, it often appears implicitly and in a secondary manner, with greater emphasis placed on the specific concepts of each discipline.